2009
DOI: 10.1002/smll.200801197
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Patterning Conducting Polymers Using Nanoimprint Lithography and Isotropic Plasma Etching

Abstract: Figure 5. SEM images of SNPs adsorbed onto the PANI dots (a) and lines (b). Scale bar ¼ 1 mm. Scale bar of the insets ¼ 500 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 38 publications
(36 reference statements)
1
41
0
Order By: Relevance
“…Recently, topographically modified electroactive surfaces have been introduced as a cell culturing platform to support growth of excitable tissue cells. There are a number of available patterning methods such as CFL, 52 NIL 49 or lift-off 25 for patterning conducting polymers. Since most of the conducting polymers are rigid (elastic modulus; PANi: 2–4 GPa, 32 PPy: 1.2–3.7 GPa, 113 PEDOT: 1.1–2.2 GPa 79 ) they can form tens of nanometer scale features with high fidelity.…”
Section: Synthetic Polymers and Their Properties/uses In Patterning Mmentioning
confidence: 99%
“…Recently, topographically modified electroactive surfaces have been introduced as a cell culturing platform to support growth of excitable tissue cells. There are a number of available patterning methods such as CFL, 52 NIL 49 or lift-off 25 for patterning conducting polymers. Since most of the conducting polymers are rigid (elastic modulus; PANi: 2–4 GPa, 32 PPy: 1.2–3.7 GPa, 113 PEDOT: 1.1–2.2 GPa 79 ) they can form tens of nanometer scale features with high fidelity.…”
Section: Synthetic Polymers and Their Properties/uses In Patterning Mmentioning
confidence: 99%
“…The patterning of the polymer film is then done by a traditional sacrificial lithography technique, which does not require any etching steps, and is therefore also more cost effective. The experimental details for the formation of a PAni or PPy layer are slightly different since different conditions yield lead to better results for each of these materials (in terms of polymerization time and film thickness) [31], according to the following procedure: For the formation of a PAni layer, the polymerizing solution consisted of a combination of the monomer, aniline (Sigma-Aldrich, St. Louis, MO, USA), and ammonium persulfate (APS) (ICN Biomedicals, Inc., Aurora, OH, USA), an oxidizing agent needed for the chemical oxidative synthesis. A 10 mL solution containing APS (40 mM) in 1 M HCl (Sigma-Aldrich) was prepared.…”
Section: Fabricationmentioning
confidence: 99%
“…Shaping these materials into functional components remains a challenge because of their high melting points and very low solubility in common solvents. A novel patterning technique combining a chemical oxidative synthesis of the polymers with standard silicon fabrication technology has recently been developed [31]. …”
Section: Introductionmentioning
confidence: 99%
“…[16] It has also been shown that NIL can be used to pattern functional materials such as conducting polymers, [17] ferroelectric polymers, [18] proteins, [19] metallic and semiconducting nanoparticles (NPs), [20] carbon nanotube composites, [21] sol-gels, [22] chalcogenide glasses, [23] and bulk metallic glasses. [24] NPs can be generated with an enormous array of surface functionality.…”
Section: Introductionmentioning
confidence: 99%